A History of Anthropology - Eriksen, Thomas Hylland (Anthropology, Culture and Society, 2013)
This is a thoroughly updated and revised edition of a popular classic of modern anthropology. Avoiding geographical bias, the authors provide summaries of 'Enlightenment', 'Romantic' and 'Victorian' anthropology, from the cultural theories of Morgan and Taylor to the often neglected contributions of German scholars. The ambiguous relationship between anthropology and national cultures is also considered, and the growth of distinctive national styles in anthropological research is highlighted.A History of Anthropology is an unparalleled account of theoretical developments in anthropology from the 1920s to the present, including functionalism, structuralism, hermeneutics, neo-Marxism and discourse analysis. Major anthropologists are provided with brief biographies and key debates are covered such as those concerning totemism, kinship and globalisation.This essential text on anthropology is highly engaging, authoritative and suitable for students at all levels.